(untitled) (Indian Journal of Veterinary Pathology, 2024)
Hemangiosarcomas are aggressive, malignant tumours derived from endothelial cells. Two dogs, a 10 years old male Labrador and a 5 years old female German shepherd were presented in with history of inappetance and abdominal distension. Blood examination and peritoneal fluid cytology were performed. Blood smear examination revealed anaemia with several acanthocytes, neutrophilic leucocytosis and thrombocytopenia. Further cytological examination of peritoneal fluid showed pleomorphic epithelioid cells in clusters with cytoplasmic punctate vacuolation and erythrophagocytosis along with binucleated or multinucleated cells suggestive of hemangiosarcoma. Thus cytology may prove as a preliminary diagnostic aid for hemangiosarcoma.